Testing the monster chip. - Zorian, Y. (IEEE spectrum)
The market-driven electronics industry never slackens. Thanks to the swift advance of semiconductor technology, companies can and continually do introduce products with more functions, higher reliability, lower costs and at shorter intervals. ICs are considered the foundation of even traditionally nonelectronic products. So cheap are they, and so widely available, that whole industries now live off integrating ever more functions into ever smaller packages, even to creating entire systems-on-a-chip. This paper describes how such chips with 100 million transistors demand a new approach to testing-complementary embedded and external test